Evaluation of the Serum Level of Sex Hormones in Obese Women with Polycystic Ovary Syndrome in Anbar Province - Abdulkarim, Abdullah; Abdul Ghafour, Khalid; Murshid, Rafal (Journal of Biomedicine and Biochemistry, 2023)
Objective This study aimed to learn more about Polycystic Ovarian Syndrome (PCOS) and the connection between body fat percentage and hormonal imbalance.Subjects and methods The Control (N = 60) and PCOS (N = 90) groups comprised inactive women. Single-use needles were used in the (10 ml) blood collection process. Venous blood was collected from the females approaching consulting clinic at Al-Ramadi Teaching Hospital for Women and Children in Anbar, Iraq, from February 2022 to July 2022. The PCOS group was segregated into three subgroups (25–30%, 30–35%, and 35–40%) based on body fat percentage. In addition to tests of follicle- stimulating hormone (FSH), luteinizing hormone(LH), and anti-Mullerian hormone(AMH), the approach also included measurements of body fat in- dex, neck circumference, waist-hip ratio, and Body fat percentage.Results The mean ±SD of LH level in serum in the subgroups of PCOS patients (25%-30%, 30%-35%, 35%- 40%) and control group was (47.30±7.76, 62.04±7.78, 61.65±7.73) and (19.83±3.79) respectively. While the mean±SD of AMH level in serum in the subgroups of PCOS patients (25%-30%, 30%-35%, 35%- 40%) and control group was (989.86±196.35, 1140.69±208.44, 1125.22±217.87) and (599.13±171.23) respectively. The mean± SD of LH level in serum in the subgroups of PCOS patients (25%-30%, 30%-35%, 35%-40%) and control group was (20.54±3.65,21.88±3.17 and 21.67±3.64 ) and (35.31±3.73) respectively at P≤0.05.Conclusion Our results show that PCOS and body fat percentage di- rectly impact FSH, LH, and AMH concentrations, as well as anthropomet- ric measurements.